Massive outbreak of poliomyelitis caused by type-3 wild poliovirus in Angola in 1999 - F. Valente; M. Otten; F. Balbina; R. Van de Weerdt; C. Chezzi; P. Eriki; J. Van-Dúnnen; J.-M. Okwo Bele
The largest outbreak of poliomyelitis ever recorded in Africa (1093 cases) occurred from 1 March to 28 May 1999 in Luanda, Angola, and in surrounding areas. The outbreak was caused primarily by a type-3 wild poliovirus, although type-1 wild poliovirus was circulating in the outbreak area at the same time. Infected individuals ranged in age from 2 months to 22 years; 788 individuals (72%) were younger than 3 years. Of the 590 individuals whose vaccination status was known, 23% had received no vaccine and 54% had received fewer than three doses of oral poliovirus vaccine (OPV). The major factors that contributed to this outbreak were as follows: massive displacement of unvaccinated persons to urban settings; low routine OPV coverage; inaccessible populations during the previous three national immunization days (NIDs); and inadequate sanitation. This outbreak indicates the urgent need to improve accessibility to all children during NIDs and the dramatic impact that war can have by displacing persons and impeding access to routine immunizations. The period immediately after an outbreak provides an enhanced opportunity to eradicate poliomyelitis. If continuous access in all districts for acute flaccid paralysis surveillance and supplemental immunizations cannot be assured, the current war in Angola may threaten global poliomyelitis eradication.